Alternative energy sources as an integral part of energy cost reduction - Kaliakparova, G.Sh.; Gridneva, Y.Е.; Amankeldi, N.A.; Parmanova, R.S.; Beketova, K.N. (BUKETOV BUSINESS REVIEW, 2024)
Object: To show the various alternative (renewable) energy sources used in the global space. Conventional energy sources with emissions from them are non-renewable and affect the planet's ecology. On the other hand, alternative energy sources are naturally renewable and practically non-exhaustible. Methods: Descriptive method — alternative energy sources were disclosed, economic aspects of their impact were studied; analytical method shows the efficiency of renewable energy sources; comparison method helps to investigate the feasibility of alternative energy sources. Findings: In the article the main alternative energy sources were showed, possible economic risks and their impact on the introduction and use in connection with economic instability were studied, the effectiveness of their impact on the development of the country's economy as a whole was investigated. Conclusions: The analysis of existing alternative energy sources allowed characterizing the available advantages. Reducing the use of natural minerals, as well as reducing dependence on them, can lead to reduced search and additional extraction. Renewable energy sources depend on financial mechanisms such as subsidies, tax incentives and investments. In the process of research, the use of alternative energy sources abroad was studied. We would like to note that the world experience of renewable energy sources use shows an important alternative solution to already available energy sources from the economic point of view.